The knowledge transmission mechanism and austerity. Why policy makers, rather than academic economists, made macroeconomic errors in 2010 - Wren-Lewis, Simon (Düsseldorf, 2015)
"How do economic policy mistakes happen? One view is that policy makers are benevolent, and errors arise because economic theories are inadequate. Another is that policy makers pursue sectional interests that may have no relation to any academic consensus on good policy. This paper examines a third alternative: policy makers want to do the right thing (although they have political preferences), and the academic consensus is correct, but policy makers do not follow it because they rely on imperfect intermediaries. I use this framework to examine the global switch to fiscal austerity in 2010."